Women and Race in Contemporary U.S. Writing - Reames, K. Lynch. author. aut Link
X, 189 p.
Keywords: This study discovers how contemporary writers have imagined possible relationships between African American and white women that overcome the stereotypical patterns of racism, using novels and autobiographies and focusing on works by William Faulkner, Lillian Hellman, Audre Lorde, Kaye Gibbons, Elizabeth Cox, Sherley Anne Wiliams, and Toni Morrison.